2020
DOI: 10.1371/journal.pone.0229617
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an association between clinical INSTI-related body weight gain and direct interference with MC4 receptor (MC4R), a key central regulator of body weight

Abstract: An increasing prevalence of overweight and obesity in people living with HIV has been associated with initiation of antiretroviral therapy with integrase strand transfer inhibitors (INSTIs). An off-target inhibition of the endogenous ligand binding to the human melanocortin 4 receptor (MC4R) has been suggested as a potential mechanism for clinical body weight gain following initiation of dolutegravir, an INSTI. In this study, we interrogated several INSTIs for their capacity for antagonism or agonism of MC4R i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…In contrast, the results of the CoRIS cohort study support our findings that TAF itself is associated with weight gain by showing significantly greater weight gain with TAF in patients newly commencing treatment with TAF or TDF. [31] Various other explanations for different observations in weight changes related to cART include a return-to-health effect in the first years after therapy initiation, altered regulation of appetite, and interactions with the MC4 receptor [ 19 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the results of the CoRIS cohort study support our findings that TAF itself is associated with weight gain by showing significantly greater weight gain with TAF in patients newly commencing treatment with TAF or TDF. [31] Various other explanations for different observations in weight changes related to cART include a return-to-health effect in the first years after therapy initiation, altered regulation of appetite, and interactions with the MC4 receptor [ 19 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors present an elegant description and figure detailing potential ways (at least 4) by which this could occur. However, another group tested and refuted this theory [ 73 ]. They evaluated the effects of INSTIs on MC4R in an in vitro cell-based assay and found that INSTIs indeed antagonize MC4R, but only at supratherapeutic concentrations, and thus concluded that this is unlikely to explain INSTI-induced weight gain.…”
Section: Integrase Strand Transfer Inhibitorsmentioning
confidence: 99%
“…It has been shown that DTG inhibits the binding of amelanocyte-stimulating hormone (aMSH) and melanocortin 4 receptor (MC4R) in the hypothalamus; this might promote hyperphagia (147,148). However, the serum DTG levels in patients are much lower than those required for hyperphagia (149).…”
Section: Local Effectsmentioning
confidence: 99%